Verifying Machine Learning conclusions for securing Low Inertia systems. (June 2022) - Bellizio, Federica; Bugaje, Al-Amin B.; Cremer, Jochen L.; Strbac, Goran
Abstract: Machine Learning (ML) for real-time Dynamic Security Assessment (DSA) promises a probabilistic approach to secure lower safety margins and costs. However, future systems with a high share of renewables have low inertia and converter-interfaced devices resulting in faster dynamics. Past research on ML-based DSA used high inertia systems to study 'the best' ML data, features, and models building upon each other's work for decades. Seldom has ML-based research for DSA questioned whether the underlying assumptions for (and the conclusions of) these studies are still valid for low inertia systems. This work studies exemplary changes in assumptions (and conclusions) for ML-based DSA when moving from High Inertia (HI) to Low Inertia (LI) systems. The dynamical system of the LI system is brought in perspective with the most typical ML-based approaches, which are organised in sequential steps. The steps consider the generation of the training database, the data pre-processing and feature selection, the model training and validation. This work analyses each step individually for the changed assumptions in the dynamical LI system, and subsequently, a case study provides the evidence that considering a LI system to identify the 'best' ML approaches is important. The case studies on IEEE 14 and 68 bus systems confirm that LI systems must be optimised for security (otherwise, they result in 80% less security than HI systems). The key findings, however, are that using ML makes significantly more sense in LI systems than in HI systems as the LI dynamics are in shorter timescales (and the advantage of ML is to predict security in milliseconds) and that secure/insecure operations can be separated more straightforwardly in LI systems as ML increases the accuracy by up-to 40% towards close to 100% when using neural networks. Highlights: A dynamic model for low inertia power systems. Impact analysis of the newly introduced low-inertia dynamics on ML-based real-time dynamic security assessment. Case studies on the IEEE 14 and 68 bus system to compare the performance of ML-based approaches in high and low inertia systems. High performance of ML-based security in low inertia systems.